EL MOSAICO DE LAS LENGUAS DE BOLIVIA: Las lenguas indígenas de Bolivia ¿Obstáculo o herramienta en la creación de la nación de Bolivia? - Cancino, Rita (Diálogos Latinoamericanos, 2008)
In Bolivia, the Spanish language as the language of the conquerers was the only official language for centuries while the native languages almost disappeared. The purpose of the new president in Bolivia since 2006, Evo Morales, is to create a nation by using a language policy in which the original languages, Quechua, Aymará y Guaraní are also official languages, together with more than 30 other native languages. The new Bolivian state will be bilingual as all Bolivians have to speak two languages: The Spanish speaking groups have to learn a native language, and the native groups have to learn Spanish. This is done in order to create a common identity among the many different people and cultures represented in Bolivia, but in his intent to give back their identity to the original people by recognizing the native language, Morales has met serious problems from the other social groups.